Identification of bacterial communities associated with needle mushroom (Flammulina filiformis) and its production environment - Liu, Zhenghui; Cong, Yunlong; Sossah, Frederick Leo; Sheng, Hongyan; Li, Yu (Frontiers in Microbiology, 2024)
Flammulina filiformis is an important edible and medicinal mushroom widely cultivated in East Asia, with its quality and health strongly influenced by associated microbial communities. However, limited data exist on the bacterial communities associated with F. filiformis cultivation in Chinese farms. This study investigated bacterial communities associated with F. filiformis and its production environment using high-throughput 16S rRNA gene amplicon sequencing and culture-dependent methods. A total of 42 samples were collected from farms in Jilin and Guizhou provinces, China, for microbial community profiling. The analysis revealed diverse bacterial phyla, including Proteobacteria, Firmicutes, Bacteroidetes, Actinobacteria, and Cyanobacteria. Genera such as Pseudomonas, Lactobacillus, Acinetobacter, Flavobacterium, and Phyllobacterium were identified, with notable regional variations in the relative abundance of Pseudomonas and Lactobacillus. Pathogenic species, including Pseudomonas tolaasii, Ewingella americana, Stenotrophomonas maltophilia, Pseudomonas sp., Lelliottia amnigena, and Janthinobacterium lividum, were identified through phenotypic, biochemical, and molecular analyses. Pathogenicity tests confirmed the disease-causing potential of P. tolaasii, E. americana, and J. lividum in F. filiformis. These findings highlight regional differences in bacterial community composition and emphasize the need for tailored management practices. This study contributes to safe, high-quality mushroom cultivation and provides insights into improved cultivation practices, including Mushroom Good Agricultural Practices (MGAP).